Огненный шторм: [роман] / Дэвид Класс - Класс Дэвид (Опасные игры, 2008)
Экземпляры: аб. (2009) / Инвентарный номер: 52557 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 47 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)-445